Estrutura genética intrapopulacional e dispersão de pólen em Hancornia speciosa Gomes (Apocynaceae) - Costa, Camila Fernanda (2013)
Hancornia speciosa (Apocynaceae) is a fruit species which has a wide distribution in areas of Cerrado vegetation type restricted sense. Its flowers have a complex pollination mechanism and unique, co-adapted to pollination by moths and butterflies and their fruits are dispersed by mammals large and medium-sized. It has high economic potential and its use has been conducted in an exploratory way. To implement conservation programs, breeding and enabling the commercial use of species, knowledge about the genetic variability, the spatial genetic structure, the reproductive system and gene flow in natural populations are needed. In this context, in the present study was performed the molecular characterization of the genetic variability in three stages of individuals (adults, juveniles and seedlings) and the assessment of genetic structure spatial (adults and juveniles), of the system of crossing and of the gene flow via pollen in a subpopulation of Hancornia speciosa located in the State Park of Serra de Jaragua, Jaragua-GO. To this end, 113 adults and 100 juveniles were sampled and georeferenced in an area of approximately 2.5ha. Of the total number of adults, 20 trees were selected matrices to obtain seedlings and formation of families of open pollination. Genomic DNA was obtained from the leaves of all individuals (adults, juveniles and seedlings) and was amplified with the use of seven microsatellite loci for obtaining of genotypes. The analyzes of genetic diversity, of spatial structure, rates of cross-fertilization and distance of dispersal of pollen were obtained from these genotypes. The total number of alleles at seven loci evaluated was 125, with an average of 17.8 alleles per locus. For adults the mean allele was 15.8, for the juveniles was 13.5and the seedlings were 11alleles. The average total values of heterozigosidade expected (He) and observed (Ho) were equal to 0.750 and 0.698, respectively. In adults He = 0.750 and Ho =0.714, in juveniles He =0.744 and Ho =0.679 and in seedlings He = 0. 712 and Ho =0. 763. These values indicate that the subpopulation evaluated presents high levels of genetic diversity. The fixation index(f) waspositive and significantforthe generations ofadults(0.052, p <0.05)andjuvenile(0.087, p <0.05), indicating the existence of inbreeding in this subpopulation. The analysis of spatial autocorrelation evidenced that kinship is weakly related to the geographical distance in in bothstagesof lifeevaluated (adults: b= -0.00223, R2 = 0. 000514, p < 0.05 and juveniles: b: - 0.00440, R2 = 0.00148489; p < 0.001).Concomitantly the values of Sp were low and the size of neighborhoods (Nb) were high for the two generations. This result shows that there is no restriction of gene flow via seed and corroborates the hypothesis that the dispersal by animals have high potential to disperse the seeds over long distances.The rates of crossfertilization multilocus (tm= 1.000) and single locus (ts = 0.972 a 1.29) were high and significantly different from zero in all families. The difference in the rate of the crossfertilization multilocus and single locus combined for all families analyzed (tm-ts = 0. 077) was also positive and significant, suggesting that 7% of crossings that occur in this population are between related individuals. The correlation of selfing negative(rs=-0.999), indicates absence of selfing and the correlation of paternity(rp=0.107) not significantly different from zero (SD = 0.135) shows that this subpopulation no full siblings. Every subpopulation resulting outcrossing and individuals are evaluated relatives at least to the 15 level of half-brothers. The paternity analysis assigned pollen donors to 75.2% (64) seedlings, and 24 (37.5%) assignments at a confidence level of 85%, 30 (46.8%) assignments at 95% probability assignments and 10(15.6%) at a confidence level of 99%.This low assignment can be explained by sampling: due to the size of the total area of the population and distribution in aggregate, many individuals may not have been sampled. Moreover, the loci battery used in this analysis could not demonstrated the optimal values for the combined exclusion. Although the maximum distance of pollination has been of 292m and covers the entire area evaluated, most events of pollination (77%) occurred at distances less than 200m. The flowering in mass, the distribution in aggregate and the floral structure are the main responsible for predominance of events of cross-pollination at short distances.